2021
DOI: 10.3390/plants10112510
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-Driven Discovery of an Introduced Species and Two Malaysian Piper betle L. Variants

Abstract: The differences in pungency of “sirih” imply the probable occurrence of several variants of Piper betle L. in Malaysia. However, the metabolite profiles underlying the pungency of the different variants remain a subject of further research. The differences in metabolite profiles of selected Malaysian P. betle variants were thus investigated; specifically, the leaf aqueous methanolic extracts and essential oils were analyzed via 1H-NMR and GC-MS metabolomics, respectively. Principal component analysis (PCA) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Macroinvertebrates are one of the most notable biological indicators for freshwater quality, especially for river ecosystems. However, there are a few studies such as Deborde et al (2016), Kim et al (2016), Brogna et al (2018), Foomani et al (2020), and Edegbene et al (2021) which have shown a significant relationship between forest health and river water quality. There are also studies that use other biological indicator distributions such as birds (Laiolo et al, 2011;Wade et al, 2013;Gnass Giese et al, 2015), nematodes (D'Errico et al, 2014;Nisa et al, 2021), amphibians (Jongsma et al, 2014), microorganisms (Hermans et al, 2020), fish (Gottesman et al, 2020) and mites (Meehan et al, 2019).…”
Section: The Forest Health Biomonitoring Technique-thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Macroinvertebrates are one of the most notable biological indicators for freshwater quality, especially for river ecosystems. However, there are a few studies such as Deborde et al (2016), Kim et al (2016), Brogna et al (2018), Foomani et al (2020), and Edegbene et al (2021) which have shown a significant relationship between forest health and river water quality. There are also studies that use other biological indicator distributions such as birds (Laiolo et al, 2011;Wade et al, 2013;Gnass Giese et al, 2015), nematodes (D'Errico et al, 2014;Nisa et al, 2021), amphibians (Jongsma et al, 2014), microorganisms (Hermans et al, 2020), fish (Gottesman et al, 2020) and mites (Meehan et al, 2019).…”
Section: The Forest Health Biomonitoring Technique-thematic Analysismentioning
confidence: 99%
“…Aside from that, a large diversity of species in a forest indicates that the ecosystem service and function are optimum. According to Abas (2021), biodiversity is commonly acknowledged as the primary driving factor in ecosystem function. Numerous of studies have been conducted to investigate the impact of tree species variety on several forest ecosystem services, including primary production (Moradi et al, 2019).…”
Section: Biomonitoring Technique Of the Forest Health-current Progres...mentioning
confidence: 99%
See 1 more Smart Citation